Ministers and centres of power in Nazi Germany - Fonseca, Ana Mónica (2009)
The operation of the Third Reich’s political system has always been a subject of debate in international historiography. The major division emerges when Hitler’s position within the regime is analysed. On the one hand, there are those who argue National Socialism was no more than ‘Hitlerism’: that Hitler’s role was both fundamental and determining in the prosecution of the policies that were followed—from foreign policy to racial questions (e.g. Hildebrand 1994; Bracher 1993).